2015
DOI: 10.1111/hae.12847
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, haematuria and renal functioning in haemophilia – a cross‐sectional study in Europe

Abstract: As in the general population, age and BMI were major risk factors for hypertension in people with haemophilia. Renal dysfunction was associated with hypertension, but the prevalence of renal dysfunction was not extensive and furthermore not significantly correlated with haematuria. The associations of other variables with hypertension require further studies to confirm causal relationships over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 37 publications
1
63
1
3
Order By: Relevance
“…It has been considered that microbleeding in the kidney could be an important factor predisposing to hypertension in PWH. Recently, the absence of a correlation between haematuria and hypertension was reported; however, this alone cannot exclude the possibility of microbleeding in the kidney being a factor involved in the development of hypertension, and further investigation is needed. The higher prevalence (23/29, 79.3%) of hypertension in patients with inhibitors, who show a higher tendency towards bleeding, seems to lend support to the notion of involvement of microbleeding in the kidney in the development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It has been considered that microbleeding in the kidney could be an important factor predisposing to hypertension in PWH. Recently, the absence of a correlation between haematuria and hypertension was reported; however, this alone cannot exclude the possibility of microbleeding in the kidney being a factor involved in the development of hypertension, and further investigation is needed. The higher prevalence (23/29, 79.3%) of hypertension in patients with inhibitors, who show a higher tendency towards bleeding, seems to lend support to the notion of involvement of microbleeding in the kidney in the development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of the renal status in 26 people with hemophilia (age range, 17‐82 years), Beck and Evans reported a history of macroscopic hematuria in 69% of the patients. Later studies confirmed the high prevalence of hematuria among people with hemophilia . Although usually considered a benign condition, studies have found macroscopic hematuria associated with a reduction in renal function and an increased risk of hypertension, comorbid conditions that may complicate treatment in aging people with hemophilia.…”
Section: Introductionmentioning
confidence: 87%
“…As several studies have identified macroscopic hematuria as a risk factor for renal damage, an assessment of treatment that may prevent hematuria is important. Using data from the Age‐Related Developments and Comorbidities in Hemophilia (ADVANCE) Working Group's H3 Study, we examined whether frequent prophylactic factor replacement therapy corresponded with a reduced occurrence of macroscopic hematuria in this large cohort of people with hemophilia.…”
Section: Introductionmentioning
confidence: 99%
“…On multivariate analysis, HIV infection and hypertension were strongly associated with both ARD and CRD whilst inhibitors were associated with ARD, and increasing age with CRD. Although a recent European epidemiological study did not find a correlation between haematuria and renal dysfunction in PWH (Holme et al , ), the risk of haematuria increases with age and can be a significant problem for PWH and health care professionals. Urology referral is recommended for patients with haematuria and mild haemophilia or recurrent haematuria in patients of any severity; it should also be considered for elderly patients in order to exclude an underlying malignancy.…”
Section: Renal Diseasementioning
confidence: 94%